Evaluasi Kebijakan E-Filing Dalam Pelaporan Surat Pemberitahuan Tahunan Wajib Pajak Orang Pribadi - Rizqia Alfiana; Ananta Prathama (SOCIETAS, 2022)
The Directorate General of Taxes continues to strive to provide the best service for the community so that it is expected to encourage the public to be aware and orderly as taxpayers, as evidenced by the utilization of information and communication technology through the implementation of the tax e-system. One of them is the application of e-filing. This study aims to evaluate the e-filing policy in reporting individual taxpayer annual notices at KPP Pratama Surabaya Mulyorejo. The research method used in this study is a qualitative research method. The results of the study show that: 1) effectiveness, the implementation of e-filing has been effective. Because there is an increase in the number of individual taxpayers who report their annual tax returns via e-filing every year. 2) efficiency, the implementation of e-filing is already efficient. It can be said that this is efficient because the implementation of e-filing requires little effort from its resources. 3) adequacy, in the implementation of e-filing has solved the problem of tax compliance in the annual tax return reporting. 4) the leveling, distribution of facilities/infrastructure and socialization carried out by the tax authorities have been evenly distributed and can be accepted by each taxpayer. 5) responsiveness, taxpayers respond positively and satisfied. Taxpayers are satisfied and helped by the existence of e-filing. 6) accuracy, e-filing is very beneficial for the tax authorities and taxpayers, so that the objectives with the results to be achieved are appropriate.